UM ESTUDO SOBRE CRITÉRIOS DE AVALIAÇÃO DE SUCESSO NA IMPLEMENTAÇÃO DE SISTEMAS ERP - Freitas, Reinaldo José de (2013)
This study aims to identify criteria that can be used to evaluate the successful implementation of ERP (Enterprise Resouce Planning) systems in large Brazilian companies. Thus, after evaluation of 74 articles during the literature review, 34 criteria used in the evaluation of successful implementation of ERP systems were identified. These criteria were evaluated by 111 Brazilian experts in ERP systems through electronic form created in EncuestaFácil site. Confidentiality of responses was assured through a service contract with the site. Upon completion of the study, it was calculated the rate of content validity (Content Validity Ratio - CVR) for each criterion, being selected 25 criteria considered valid for large Brazilian companies by the expert respondents. Also it was used the analytic hierarchy process (Analytic Hierarchy Process - AHP) in a large Brazilian company in the energy sector with the objective of defining the weights of each selected criteria.